USE OF CORRELATION AND REGRESSION ANALYSIS IN THE ENTERPRISE MARKETING SYSTEM - SUVOROVA, Svitlana; CHUMAKOV, Kyrylo (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The relevance of the application of analytical methods in the marketing system of the enterprise lies in the need for effective management of complex relationships between marketing variables and key indicators of success in the conditions of the modern business environment. Intensified competition, rapid technological changes, instability of economic and political conditions create challenges that must be systematically analyzed to ensure stable development and competitiveness of the enterprise. In this context, the use of correlation-regression analysis allows enterprises to systematize and analyze complex dependencies between marketing indicators, which became a necessity in conditions of high competition and the spread of the consequences of war to all areas of business activity. The article defines and analyzes the importance of correlation and regression analysis as a tool for managing enterprise marketing strategies in the current competitive market environment. The current problems of marketing activities caused by the consequences of the pandemic and the ongoing war are investigated. The author identifies the need for a systematic approach and implementation of new solutions, including constant monitoring of changes in market demands and flexible adjustment of marketing strategies. The article reveals a tendency to increase the average share of expenses for marketing activities of enterprises, as well as investments in modern marketing solutions and tools. The paper also develops and systematizes a methodological approach to the use of correlation and regression analysis, which contributes to improving the efficiency of management decisions in the field of marketing. In addition, the most common and relevant areas of application of correlation and regression analysis in the marketing activities of enterprises are systematized. The results of the study emphasize the importance of this method for the development of strategic marketing initiatives and maintaining the competitiveness of an enterprise in the current market environment.